2013
DOI: 10.1074/jbc.c112.446823
|View full text |Cite
|
Sign up to set email alerts
|

Serines in the Intracellular Tail of Podoplanin (PDPN) Regulate Cell Motility

Abstract: Background: PDPN is a transmembrane receptor that promotes cell migration, but modifications that regulate its effects are not known. Results: PKA can phosphorylate PDPN, nonphosphorylatable PDPN promotes cell migration, and phosphomimetic PDPN fails to promote cell migration. Conclusion: PKA can phosphorylate PDPN to decrease cell migration. Significance: PDPN effects on cell motility are important for processes including embryonic development and cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 39 publications
7
89
0
Order By: Relevance
“…Therefore, our data indicate PDPN to be an antiapoptotic factor, which may be associated with pathophysiological processes in renal diseases such as AngII-induced hPC apoptosis. These findings are substantiated by the data of other investigators [9,[48][49][50]. In cancer settings Yamaki et al [50] showed that overexpression of PDPN in human mesothelioma cells increased their resistance to cis-diamminedichloroplatinum (II)-induced apoptosis, whereas overexpression of PDPN in fibroblasts increased the viability of melanoma cells in coculture experiments [48].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Therefore, our data indicate PDPN to be an antiapoptotic factor, which may be associated with pathophysiological processes in renal diseases such as AngII-induced hPC apoptosis. These findings are substantiated by the data of other investigators [9,[48][49][50]. In cancer settings Yamaki et al [50] showed that overexpression of PDPN in human mesothelioma cells increased their resistance to cis-diamminedichloroplatinum (II)-induced apoptosis, whereas overexpression of PDPN in fibroblasts increased the viability of melanoma cells in coculture experiments [48].…”
Section: Discussionmentioning
confidence: 55%
“…These findings are substantiated by the data of other investigators [9,[48][49][50]. In cancer settings Yamaki et al [50] showed that overexpression of PDPN in human mesothelioma cells increased their resistance to cis-diamminedichloroplatinum (II)-induced apoptosis, whereas overexpression of PDPN in fibroblasts increased the viability of melanoma cells in coculture experiments [48]. Moreover, Peterziel et al [49] reported that inhibition of PDPN expression leads to reduced proliferation of glioma cells in vitro.…”
Section: Discussionmentioning
confidence: 60%
“…CFM-4 also enhanced expression of serine-phosphorylated cell surface sialo-glycoprotein podoplanin that regulates cell motility and integrity, while promoting cleavage of vimentin in MPM cells [69]. In light of the fact that serine phosphorylation in the short cytoplasmic domain of podoplanin interferes with the processes of cellular motility [72], podoplanin phosphorylation and cleavage of vimentin in the CFM-4-treated MPM cells would suggest for motility and metastasis-inhibitory properties of CFMs [69]. Our gene-array based analysis in MB cells revealed that CFM-4 enhanced the expression of neurotrophin (NTF3), while depletion of NTF3 expression inhibited MB cell apoptosis by CFM-4, suggesting a potential therapeutic window with CFM-4 mediated apoptosis through NTF3 signaling in MB cells [68].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent articles (Acton et al, 2014;Astarita et al, 2014) The mechanism proposed by the authors about the role of Ser-167 must be taken with caution, as it is based on the results of Krishnan et al (2013) who used double mutants of Ser-167 and Ser-171 in in vitro systems.…”
Section: Signaling and Molecular Mechanismsmentioning
confidence: 99%
“…In particular, Ser-157(167) is predicted to be phosphorylated by PKA and PKC. Using the mouse protein, Krishnan et al (2013) observed in vitro phosphorylation of the CT peptide by PKA. By using cells transfected with WT, double Ser-167 and Ser-171 nonphosphorylatable (SS  AA) and phosphomimetic (SS  DD) mutants, it was shown that the AA mutant enhanced cell migration, whereas the DD mutants decreased it.…”
Section: Phosphorylationmentioning
confidence: 99%